Development of Sustainable Catalytic Pathways for Furan Derivatives - Liu, Xiaofang; Yu, Dayong; Yang, Wenjia; Zhang, Qiuyun; Wu, Hongguo; Li, Can (Frontiers in Chemistry, 2021)
Biomass, the only globally available, renewable feedstocks of organic carbon, is supposed as alternative to fossil fuels, which can be efficient utilized for the production of various building blocks in accordance to the green and sustainable chemistry. In this review, recent progresses such as the transformation of carbohydrates (C5 or C6 sugar, inulin, cellulose) and derivatives (furfural, HMF) for significant platform chemicals over polyoxometalates, zeolites, non-noble metal and ionic liquids in single or multiphases are evaluated.